Pengaruh Jenis Pisang (Musa Paradisiaca) Terhadap Karakteristik Tapai Pisang di Banyuwangi - Helmy Ahfas; Rosyid Ridho; Laela Nuraini (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2019)
The general objective of this study was to determine the effect of banana species on organoleptic properties in tapai. The specific purpose of this study was to determine the differences in tapai nutritional content of several types of bananas and find out the type of banana suitable for tapai banana.This experiment uses RAL consisting of 4 types of bananas including kepok banana, awak banana, kayu banana and raja / sajen. The results showed that the organoleptic test most favored by panelists was kepok banana andfrom chemical tests showed that kayu banana had the highest protein content than the other banana species which was 1.21% and raja / sajen had the highest sugar content than the type the other banana is 12.38%.